Moringa oleifera Leaf Extract and (Amorphophallus muelleri Blume.) Glucomannan Effects on Obese White Rat Feed Intake and Body Weight - Wati, Dini Prastyo; Endang Setyaningsih (International Journal of Ecophysiology, 2024)
Obesity significantly raises the rates of illness and death in humans due to its association with several health conditions such as cardiovascular disease, hypertension, hypercholesterolemia, type 2 diabetes mellitus, osteoporosis, depression, breast cancer, and colon cancer. This study aims to determine the effect of Moringa oleifera leaf extract and glucomannan (Amorphophallus muelleri Blume.) on feed intake and body weight of obese white rats. This study used an experimental method with a pretest-posttest-only control grub design using 24 white male rats of the Wistar strain aged 8 weeks which were divided into 2 control groups, namely positive(K1) and negative(K2) and six treatment groups with extract doses Moringa oleifera leaves and glucomannan (Amorphophallus muelleri Blume.) 100mg/kgBW:100mg/kgBW(K3), 80mg/kgBW:120mg/kgBW(K4), 120mg/kgBW: 80mg/kgBW(K5), 50mg/kgBW:50mg/kgBW(K6), 40mg/kgBW:60mg/kgBW(K7), and 60mg/kgBW:40mg/kgBW(K8). Data analysis on body weight and feed intake used the SPSS ANOVA test and paired T-test. The results of the paired T-test (p<0.05) showed that Moringa oleifera leaf extract and glucomannan (Amorphophallus muelleri Blume.) significantly reduced body weight and feed intake. In conclusion, administration of Moringa oleifera leaf extract and glucomannan (Amorphophallus muelleri Blume.) in group K4 (80 mg/kgBW Moringa oleifera leaf extract: 120 mg/kgBW glucomannan Amorphophallus muelleri Blume) can reduce feed intake (4.29 g) and body weight (36.67 g) effectively.